The conservation biology of the Dugong (Dugong dugon) and its seagrass habitat in Sabah, Malaysia : A basis for conservation planning - Leela Rajamani Ramnath Rajamani (2009)
Prior to 1999, dugongs were rarely observed in Malaysia. This first comprehensive study of dugongs and their related seagrass habitats in Sabah, investigated the local stakeholder environment, the abundance and distribution of dugongs, identified and monitored threats to dugongs, and mapped seagrass habitats relevant to dugongs. The study was conducted in two spatial scales namely, 1) Regional (to determine dugong distribution in Sabah) (excluding Tawau) 2) Local - to determine local dugong abundance, conduct seagrass mapping and community surveys at two study sites Banggi island and Mantanani island. Community surveys consisted of a census, interview surveys, a dugong monitoring programme and participant observation. This information was used to determine stakeholder characters, and their perceptions of the researcher, research project, dugongs and seagrasses. Local ecological knowledge (LEK) of dugongs and seagrasses was also sought. The abundance, composition and habitat area of seagrass was assessed using a method of visually estimating aboveground seagrass biomass at sites along one kilometre transects perpendicular to the coast. Biomass was estimated every SO metres in shallow areas (up to 5 metres depth) and every 100 metres in deep areas (greater than 5 metres depth). These sites later form the basis of seagrass meadows using GIS applications. Standardised aerial surveys were conducted regionally for the coastal waters of Sabah to determine dugong distribution patterns. The communities of Banggi and Mantanani are economically disadvantaged, practise destructive fishing and have little understanding of ecological processes and concepts of conservation. However, the reasons for dugong decline are known. Appreciation of the aesthetic value of dugongs within the communities is varied. However, the community appears to have adequate local knowledge of the dugong having cultural linkages through a dugong myth. Approximately, 70% of the total population is young below the age of 30, who could be receptive to new ideas. Outside influences from the media is widely available to the community. The community is able to develop a relationship with the researcher and participate cordially in research activities. Dugong numbers are very low in Sabah. Fifty two dugongs were sighted in Sabah excluding Tawau. Based on these results, crude estimates of minimal count are between 688 and 1376 dugongs residing in coastal Sabah. Key dugong areas were identified to be Brunei Bay, Labuan Island, and Sandakan Bay. Banggi Island and Mantanani Island supports a small population of dugongs respectively. Based on this study, dugongs were subject to threats, which were mostly anthropogenic. They were 1) blast fishing, 2) incidental entangling in nets and 3) unsupervised tourism and vessel strikes. The number of mortalities in Sabah ( especially in Banggi Island), are high compared to dugong abundance results obtained in this study. When Potential Biological Removal (PBR) estimates were compared to crude estimates of yearly mortality, it is confirmed that dugong populations are declining. Ten species of seagrass from two families were found in Banggi Island and Mantanani Island. These include Halophila ova/is, Halodule uninervis (broad and thin variety), Thalassia hemprichii, Cymodocea rotundata, Halophila decipiens, Haloph11a spinulosa, Cymodocea serrulata, Syrlngodium isoetifolium, and Enha/us acoroides. A new unidentified species of Halophila was collected in Molleangan Island, west of Banggi Island. Approximately, 415 ha and 112 ha of seagrass meadows were mapped in Banggi island and Mantanani island respectively g1v1ng a total of 527 ha of seagrass available for dugong consumption. The information obtained on the local communities, seagrass and dugong provided the basis to inform a comprehensive conservation plan in Sabah. Key conservation strategies include a dialogue and community education programme, provision of alternative livelihoods, improving enforcement to prevent illegal fishing methods, comanagement of dugong and seagrass resources, stringent controls on ecotourism and vessel strikes, zoning of seagrass in marine protected areas and further research. As the dugong is a migratory species, conservation management at an international level with the neighbouring state of Sarawak, and countries of Brunei, the Philippines and Indonesia is necessary.